The Effect Of Profitability, Liquidity, Asset Structure, And Dividend Policy On Capital Structure : (Case Study Of Manufacturing Listed On The (Bei) For The Period 2018 - 2022) - Marpaung, bintangsahala0203; Marpaung, Annaria Magdalena; Hasibuan, David H.M.; Hilman Fauzi, (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
Abstract The purpose of this study is to find out if capital structure to profitability, liquidity, asset structure, and dividend policy. The research sample consists of 9 companies selected based on a purposive sampling technique with a period of 5 years, so the total data is 45. The first step is to carry out Descriptive Analysis to see the general picture (Character) of the data. To obtain the Multiple Linear Regression Equation and coefficient of determination, the Classical Assumption Test is carried out to ensure that the data is normally distributed. Next, we search using the T Test to assess the significance between variable X and variable Y. And the final step is the F Test to assess the significance between Variable. It is uncommon to approach the study of the dividend policy variable with the notion of dividend policy a financial decision a business makes following operations and profitability By dividing the dividend payout ratio (DPR) by profits per share, one may ascertain how much money the firm distributes as dividends to its shareholders. The company's dividend policy is evaluated using this ratio.According to some of the research findings, There exists a high and positively correlation Within Capital Structure. And Liquidity, Asset Structure, and Dividend Policy, but not Within Profitability, Liquidity, and Capital Structure. Concurrently, Capital Structure is positive and significantly impacted by Profitability, Liquidity, Asset Structure, and Dividend Policy.